Sensitivity of prenatal ultrasound for detection of trisomy 18. (17th November 2019) - Becker, David A.; Tang, Ying; Jacobs, Adam P.; Biggio, Joseph R.; Edwards, Rodney K.; Subramaniam, Akila
Abstract: Objectives: To evaluate the sensitivity of prenatal ultrasound (US) for trisomy (T18) diagnosis and describe US findings in a large tertiary care institution in the USA. Materials and methods: This was a retrospective cohort of all T18 cases diagnosed at our institution from October 2004 to October 2014 based on prenatal or postnatal genetic diagnostic testing. We included all women with a fetus affected by T18 who had a comprehensive US by a maternal–fetal medicine specialist performed at our institution. US findings were reviewed, classified by organ system, and categorized as an anomaly or soft marker. Chi-square or t -test was used for statistical analysis. Results: We included 128 cases of T18 with confirmed cytogenetic analysis −110 (86%) of which were diagnosed prenatally or suspected by cell-free DNA and confirmed postnatally, and 18 of which underwent neonatal blood sampling alone. One hundred and twenty-one (95%) had at least one abnormal US finding. Anomalies were more frequently identified on US at ≥20 weeks as compared with <20 weeks (93% versus 76%; p = .004). The mean number of findings detected per fetus was 5.1 ± 3.0. Fetuses diagnosed by postnatal sampling alone had a similar number of US exams performed and number of abnormal findings compared to those diagnosed prenatally. Conclusion: Ninety-five percent of fetuses with T18 had at least one abnormal US finding. This sensitivity of is higher than reported in most prior studies, but is not 100%, and should be considered when counseling women regarding prenatal diagnosis of T18. Rationale: Historical detection rates for abnormal sonographic findings in trisomy 18 fetuses range from 70% to 100%. These studies are limited by small sample sizes. This is a contemporary study of ultrasound findings in a large group of women with confirmed trisomy 18 by prenatal or postnatal genetic diagnosis. We provide expansive detail on soft markers and anomalies broken down by organ-system and gestational age.